To trace the active compound in mengkudu (morinda citrifolia) with anthelmintic acvtivity against Haemonchus contortus - T.B Murdiati; G Adiwinatai; D Hiladsari (Jurnal Ilmu Ternak dan Veteriner, 2000)
Intestinal parasites such Haemonchus contortus is usually controlled by management improvement and regular administration of anthelmintic. However, there is an indication of H. contortus resistance to several anthelmintic available in the market, which makes medicinal plants as an alternative anthelmintic and mengkudu or noni fruit (Morinda citrifolia) have been reported as an effective anthelmintic. To trace the active compounds responsible for anthelmintic activity against H. contortus, the mengkudu fruit was continuosly extracted into hexane, chloroform, metanol and water, followed by in-vitro study on the anthelmintic activity. The in-vitro anthelmintic activity was base on the ability of the extracts to kill the worm and the ability of the extracts to prevent egg development. The study suggested that chloroform fraction which contains alkaloid and anthraquinon have the highest anthelmintic activity and showed significant different compared to control (P≤ 0.05).   Key words: Morinda citrifolia, anthelmintic, Haemonchus contortus